THE EMPIRICAL ANALYSIS OF SOIL LIQUEFACTION IN IMOGIRI SITE, YOGYAKARTA, INDONESIA - Mase, Lindung Zalbuin (Politeknik Negeri Bandung, 2019)
A strong earthquake with magnitude of 6.3 Mw, which was later known as the JogjaEarthquake, occurred in the southern part of Yogyakarta Special Province. The earthquakehad resulted in the huge damage to the buildings, public facilities as well as triggering theground failure phenomenon, which was known as liquefaction. An empirical analysis usingthe conventional method was performed to investigate the liquefaction severity for the siteinvestigation data in Imogiri, a site with the high-level of the liquefaction damage duringthe earthquake. The peak ground accelerations varied to 0.3 to 0.4g are also implemented inthe analysis. The results show that the investigated site is dominated by sandy soils. Thesandy soil in Imogiri site is categorised as the liquefiable layer during the Jogja Earthquakeand potentially to liquefy on shallow depth. In general, this study could warn the people forthe impact of soil liquefaction if the stronger earthquake happens in the future.